Evaluation of Replacing Wheat Bran with Ensete Ventricosum Corm on Feed Intake, Weight Gain, in vitro Digestibility and Economic Efficiency of Doyogena Sheep - Abebe, Mulatu (Wachemo University, 2024)
The objective of the study is to evaluate the effect of replacing different levels of wheat bran by Ensete ventricosum corm on weight gain, feed intake, in-vitro digestion, and economic efficiency of Doyogena sheep. Forty-two Doyogena yearling rams with an initial body weight of 28.95kg (mean±SE) were randomly divided into six feeding groups of seven animals per treatment in a completely randomized block design. The experiment was conducted for 90 days of feeding trial and 14 days of adaptation. All collected data throughout the experimental period were analyzed using one-way analysis of variance (ANOVA) in the statistical analysis software SAS (9.2 version). All animals were fed on natural pastures and nuge seed cakes. The supplements were offered at the rate of 300 g/day, which were offered twice per day during morning and night; (T1)control group grazing only+120 nuge seed cake, (T2) grazing+180gwheat bran+120g nuge seed cake, (T3) grazing+135g wheat bran+120g nuge seed cake + 45g corm (T4) grazing+90g wheat bran+120 g nuge seed cake + 90g corm,( T5) grazing+45g wheat bran+120 g nuge seed cake +135g corm and T6 grazing+0 g wheat bran+120 g nuge seed cake+180gr corm.. Higher weight gain of the sheep was recorded for sixth treatment (16.5kg/90d) days. FCE was higher for those sheep fed on 180g enset corm compared to sheep fed 180g wheat bran. The partial budget analysis shows that the change in total variable cost of all treatment groups was positive, but the net return was obtained in the order of T3>T6>T4>T5>T2>T1. The result of the present study has indicated that in areas where access to wheat bran is absent, enset corms could be used as a potential alternative to replace wheat bran as long as it is economically feasible and easily accessible for smallholder production systems. Thus, based on the present finding, it can be concluded that enset corm has the potential to be a 100% replacement for wheat bran in terms of energy feed without compromising the growth performance and financial effectiveness of sheep fattening.